SP10.1.1 A retrospective study: Rectal foreign bodies, enter at your own risk…. (9th August 2022) - Chowdhury, Ashim; Havelka, Eva; O'Farrell, Eoin; Pangeni, Anang; Shrestha, Ashish Kiran
Abstract: Aims: Entrapped rectal foreign bodies (FB) are being encountered by acute surgical teams with increasing frequency and can be a challenge to manage. This study aims to highlight typical patient demographics, risk factors for presentation and management options for these patients. Methods: Between 2017 and 2021, 29 cases of rectal FB were diagnosed and managed at East Kent Hospital University Foundation trust. Retrospective data taken from theatre directory and electronic notes was used to audit patient demographics, co-morbidities, the type of foreign body and the extraction technique. Results: The majority of patients were male (87%). The patient's age ranged from 15 to 78 years, with a median age of 48 years. In the majority of cases, the FB had become entrapped during sexual activity. Nineteen patients (65%) underwent examination under GA for removal, seven patients (24%) were manually evacuated and three required a laparotomy (10.3%). Nine patients (31%) had a history of known mental health problems. The most common FB removed was a roll-on deodorant (n=5). Conclusion: Cases of rectal FB's needing surgical management typically involve male patients in their 40's. While a small proportion can have manual evacuation, the majority require examination under anesthetic and in some cases a laparotomy. While a larger study would be required for significance, it appears a history of mental health problems may predispose patients to presenting with this problem. Patients present with a wide range of foreign body type, typically items commonly found in the home, the most common being roll on deodorant.